Subsistence systems of the Late Bronze Age population in the Northwestern Crimea - Borisov A.V.; Smekalova T.N.; Zanina O.G.; Leonov L.L.; Afonin A.S.; Goroshnikov A.A.; Savelyev D.O. (Вестник археологии, антропологии и этнографии)
The subsistence systems of ancient societies included three components: [i] the resource base, [ii] the economic model and [iii] the social sphere. The article discusses the main elements of the subsistence systems of the Sabativskaya and Belozerskaya cultures of the Late Bronze Age in Northwestern Crimea. It is shown that the resource base of Late Bronze Age societies was at the modern level or exceeded it. The basis of the economy of the Late Bronze Age population was animal husbandry with a specialization in cattle breeding. The share of sheep in the herd was much lower. At the same time, a significant variation in the proportion of horses in the herd was revealed in settlements located in different landscape positions. Hunting did not make any significant contribution to the economy. Traces of fishing are very insignificant. Agriculture as a sector of the economy was absent. Gathering played a significant role in the subsistence systems. The analysis of starch grains on graters indicate the use of rhizomes of reed [Phragmites sp.] for food. Stone was widely used for cattle pens building. Hovever, in the proposed living houses, stone was used only for lining pits, while and the upper part was presumably made of leather and felt. The size and different geomorphological position of the settlements, as well as the presence of stone cattle pens and types of tools may indicate different seasonality of settlements.